PENGOMPOSAN SAMPAH DAUN KERING, ECO ENZYM DAN FERMI KOMPOS: PENGABDIAN DI DESA BEGAGANLIMO - Elly Nur Agustin; Hajidah Fildzahun Nadhilah Kusnadi (Prosiding Patriot Mengabdi, 2024)
Abundant waste will result in damage to the environment and health. Realizing this, the service was carried out with the aim that the Begaganlimo village area would not be contaminated with garbage and the agricultural sector would be better off with natural compost made. Composting is done with the help of EM4. The results obtained from composting are successful with a period of approximately 3 months for perfect results. The content obtained from the compost is the ratio of o C / N of 18, potassium 2.11% and phosphorus 0.26% with the physical properties of blackish-brown compost, smelling and textured like soil with a moisture content of 13.98%, temperature 27oC and pH 7.